INTEGRASI PENDIDIKAN ISLAM DALAM PENGEMBANGAN PARIWISATA HALAL DI INDONESIA - Aeni Nahdiyati; Suriah Yusdalifa (As-Sulthan Journal of Education, 2025)
Halal tourism is one of the fastest growing sectors in Indonesia, driven by the majority of the Muslim population and increasing awareness of the need for sharia-based tourism. Islamic education has a strategic role in shaping the understanding and skills of human resources (HR) in this sector. This study aims to analyze how Islamic education contributes to the development of halal tourism in Indonesia. The research method used is a qualitative approach with an analysis of literature relevant to halal tourism. The results of this study indicate that the integration of Islamic education in halal tourism includes a sharia-based curriculum, HR training, and halal certification based on Islamic values. These findings indicate that Islamic education can strengthen the management of halal tourism destinations through an understanding of tourism fiqh, service ethics, and halal management. Therefore, collaboration between educational institutions, the government, and the halal tourism industry needs to be strengthened to increase the competitiveness of this sector in the global arena.